The Impact of Job Insecurity on Intrinsic Motivation, Anxiety, Depression, and Job Performance of Information Technology Company Employees in Indonesia - Fersi Tase; Unggul Kustiawan (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to explore the influence job insecurity to intrinsic motivation, anxiety, and depression to job performance of information technology company employees at the operator level in Indonesia. Research conducted in 2022 is designed using the purposive sampling method involving 130 IT company employees in the satellite communication system operating sector in Greater Jakarta with a working period of more than 2 years. This quantitative research uses the Structural Equation Model (SEM) method and data were analyzed with Lisrel software. Some of the findings in this study show that intrinsic motivation positive effect on job performance, job insecurity no negative effect on intrinsic motivation and job performance. Vice versa, job insecurity has positive effect on anxiety and depression. Anxiety no negative effect on intrinsic motivation, however depression negative effect on intrinsic motivation. The managerial implications of this research are important for companies to do to suppress or reduce job insecurity what employees feel is that companies need to reduce uncertainty regarding SOPs and goals to be achieved, companies need to create a supportive work climate, focus on developing employee capabilities, and provide clarity regarding the rights employees will get for their duties in the company.